ChemInform Abstract: Asymmetric Bromine—Lithium Exchange: Application Toward the Synthesis of New Biaryl‐Diphosphine Ligands. Issue 6 (21st January 2016) - Graff, Julien; Lastawiecka, Elzbieta; Guenee, Laure; Leroux, Frederic; Alexakis, Alexandre
Abstract: Twelve novel chiral biphenyl‐diphosphine ligands, e.g. compounds (III), (V), and (VI), are prepared starting from the common precursor (I).